Efficacy of topical dexamethasone eye drops in preventing ocular inflammation and cystoid macular edema following uncomplicated cataract surgery with or without injection of a single dose perioperative subtenon triamcinolone acetonide - KAŞKAL, MERT (My University, 2022)
Purpose To evaluate the efficacy and safety of topical dexamethasone (DEX) eye drops in combination with a single perioperative subtenon triamcinolone acetonide (sTA) injection versus conventional topical DEX eye drops in the prevention of ocular inflammation and cystoid macular edema following cataract surgery. Materials and methods Medical records of 245 eyes of 245 patients who underwent uncomplicated cataract surgery were analyzed in this retrospective controlled clinical study. Topical DEX eye drops were administered to 128 eyes routinely postoperatively, and 117 eyes were given a single dose of sTA (40 mg/ml) together with topical DEX eye drops for postoperative care. Postoperative topical antibiotic prophylaxis was applied to all eyes. The primary outcomes were anterior chamber (AC) cells and flare, central macular thickness (CMT), best corrected visual acuity (BCVA), and intraocular pressure (IOP) measurements on day 7, day 30, day 90, and day 180 following surgery. Results Although CMT increased in the DEX group, no increment was observed in the DEX + sTA treated group for all follow-up periods (on day 7 (+1.3 +/- 18.6 and -8.7 +/- 21.9 mu m, p = 0.038), on day 30 (+20.5 +/- 58.4 and -4.1 +/- 25.2 mu m, p = 0.009), on day 90 (+7.2 +/- 19.9 and -5.7 +/- 30.6 mu m, p = 0.029), and on day 180 (+8.2 +/- 22.6 and -6.4 +/- 32.9 mu m, p = 0.032)). There was no significant difference in terms of AC cells and flare between the two groups during the entire follow-up period (p > 0.05). Significant improvement in BCVA was observed in the DEX + sTA group at day 30 (p = 0.008). IOP differences were comparable, and both groups had high ocular tolerance. There were no severe adverse effects recorded. Conclusions Topical DEX eye drops in combination with single dose perioperative injection of sTA have robust efficacy in preventing ocular inflammation and the development of cystoid macular edema following uncomplicated cataract surgery.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Göz Hastalıkları ve Cerrahisi; Eczacılık; Meslek Bilimleri; Farmasötik Toksikoloji; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Medicine; Surgery Medicine Sciences; Eye Diseases and Surgery; Pharmacology and Therapeutics; Professional Sciences; Pharmaceutical Toxicology; Life Sciences; Health Sciences; Natural Sciences; OFTALMOLOJİ; Klinik Tıp; Klinik Tıp (MED); TOKSİKOLOJİ; Farmakoloji ve Toksikoloji; Yaşam Bilimleri (LIFE); OPHTHALMOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); TOXICOLOGY; PHARMACOLOGY & TOXICOLOGY; Life Sciences (LIFE); Optometri; Toksikoloji; Farmakoloji, Toksikoloji ve Eczacılık (çeşitli); Oftalmoloji; Sağlık, Toksikoloji ve Mutajenez; Fizik Bilimleri; Optometry; Toxicology; Pharmacology, Toxicology and Pharmaceutics (miscellaneous); Ophthalmology; Health, Toxicology and Mutagenesis; Physical Sciences; Pseudophakic cystoid macular edema; uncomplicated cataract surgery; subtenon triamcinolone acetonide; topical dexamethasone eye drops; ocular inflammation; EUROPEAN MULTICENTER TRIAL; RANDOMIZED CLINICAL-TRIAL; DELIVERY-SYSTEM; ANTERIOR; INTRAVITREAL; OCCLUSION; SURODEX; DEPOT; Pseudophakic cystoid macular edema; uncomplicated cataract surgery; subtenon triamcinolone acetonide; topical dexamethasone eye drops; ocular inflammation